2018
DOI: 10.1093/nar/gky565
|View full text |Cite
|
Sign up to set email alerts
|

MBNL splicing activity depends on RNA binding site structural context

Abstract: Muscleblind-like (MBNL) proteins are conserved RNA-binding factors involved in alternative splicing (AS) regulation during development. While AS is controlled by distribution of MBNL paralogs and isoforms, the affinity of these proteins for specific RNA-binding regions and their location within transcripts, it is currently unclear how RNA structure impacts MBNL-mediated AS regulation. Here, we defined the RNA structural determinants affecting MBNL-dependent AS activity using both cellular and biochemical assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 77 publications
(135 reference statements)
3
28
0
Order By: Relevance
“…The branched hairpin model has implications for understanding aberrant protein interaction with expanded repeats, a central theme in the study of DM1 etiology. MBNL1 preferentially binds its epitope YGCY in an unstructured environment, which is abundant in the branched, dynamic structures that we propose, but rare in perfect hairpins (Taylor et al 2018). This notion could answer the question raised before on how MBNL1 normally interacts with mostly single-stranded targets, but nonetheless binds CUG repeat RNA that was considered highly structured (Cass et al 2011).…”
Section: Cug Repeat Stem-loop Structures As Abnormal Protein Binding supporting
confidence: 50%
“…The branched hairpin model has implications for understanding aberrant protein interaction with expanded repeats, a central theme in the study of DM1 etiology. MBNL1 preferentially binds its epitope YGCY in an unstructured environment, which is abundant in the branched, dynamic structures that we propose, but rare in perfect hairpins (Taylor et al 2018). This notion could answer the question raised before on how MBNL1 normally interacts with mostly single-stranded targets, but nonetheless binds CUG repeat RNA that was considered highly structured (Cass et al 2011).…”
Section: Cug Repeat Stem-loop Structures As Abnormal Protein Binding supporting
confidence: 50%
“…The RNA structure context was discussed as being able to affect protein binding [70]. Motif analysis of the retained introns of nucleus-localized transcripts detetced 14 enriched RBPs, in which MBNL1 has been reported to bind RNA in the CUG repeats [71] and contain two nuclear signals [72]. Previous studies have reported that the CUG repeat expansion caused nuclear aggregates and RNA toxicity, which in turn induces neurological diseases [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…A double-stranded RNA-binding protein Staufen homolog 1 (STAU1) was found to stabilize RNA structures upon binding after RNA leaves chromatin, whereas hnRNP C binding to RNA was correlated with the structural disturbance of flanking regions [ 50 ]. The aforementioned AS factor, MBNL1, forms functional complexes with specific linear and structural RNA motifs [ 172 ] but upon binding it most likely unwinds the local secondary structure of the RNA as it was shown in an in vitro footprinting assay [ 173 ].…”
Section: Cellular Modulators Of Rna Structurementioning
confidence: 99%